Nutritional and lifestyle intervention strategies for metabolic syndrome in Southeast Asia: A scoping review of recent evidence. - Sze Mun Thor; Jun Wern Yau; Amutha Ramadas (PLoS ONE)
Metabolic syndrome (MetS) is frequently associated with various health issues and is a major contributor to morbidity and mortality worldwide, particularly with its recent relevance to coronavirus disease 2019 (COVID-19). To combat its increasing prevalence in Southeast Asia, numerous intervention programs have been implemented. We conducted a scoping review on recent interventions to manage MetS among Southeast Asians using standard methodologies. Cochrane, Embase, Ovid MEDLINE, PubMed, and Scopus databases were systematically searched to yield peer-reviewed articles published between 2010-2020. We included 13 articles describing 11 unique interventions in four Southeast Asian countries: Malaysia, Thailand, Indonesia, and Vietnam. These interventions were broadly categorized into four groups: (i) nutrition (n = 4); (ii) physical activity (n = 2); (iii) nutrition and physical activity (n = 2); and (iv) multi-intervention (n = 3). Most studies investigated the effects of an intervention on components of MetS, which are anthropometry, blood pressure, glucose-related parameters, and lipid profile. Significant improvements ranged from 50% of studies reporting serum triglyceride and HDL-cholesterol levels to 100% for waist circumference. Evidence on interventions for individuals with MetS remains limited in Southeast Asia. More studies from other countries in this region are needed, especially on the effects of dietary interventions, to effectively address gaps in knowledge and provide sufficient data to design the ideal intervention for Southeast Asian populations.